Water Quality Index Analysis of Situ Cilodong, Depok, West Java Using Storet Method - Zulfa, Astri; Apriansyah, Farhan; Qonitah, Tsabitah Athifah; Vansha, Fahriza Kemal; Utami, Marcelita Putri; Bakri, Hendrawan; Hoiroh, Ziyadatul; Kamila, Afifah Intan (Universitas Nasional Jakarta, 2023)
Situ Cilodong is located in Kalibaru, Cilodong, Depok. Situ Cilodong served as a beautiful, strategic area and thus served as a local water tourism. However, the presence of a human activity causes it to contain household wastes and other fillings that leak into the body of the water. The study was intended to determine the quality of the water and was held by storet methods. Storets method work by comparing data on water quality with water quality adjusted to it in order to determine water quality status. The parameters used in this study are the physical parameters in the form of temperature and brightness, also chemical in the form of pH and DO, all parameters was measure insitu in the morning. We also do identyfication of plankton. Data retrieval times occurred periodically each week of November 2021. Based on its designation, Situ Cilodong is included in class 2. The sampling station point being used is at the inlet station, center and outlet. The result of research is that the waters at Situ Cilodong was classified as a light polluted lake based on stroret's methods score on the inlet -10 station, -8 and -10 outlets. The most frequently identified type of planton species is from the phytoplanton group.